The Impact of Various Factors on the Difficulties in Learning and Teaching Strategies for Histology - Mohammedsaleh, Zuhair M (International journal of morphology, 2024)
Histology is considered one of the most important but challenging topics in health sciences. Deficiencies in teaching and general histology directly affect the student's understanding, performance and promote dynamism and integration while covering the primary curriculum. The goal of the current study was to assess and provide a better experience of difficulties in learning histology, examine some standard teaching strategies, and determine how to implement suitable changes to improve the curriculum from students' perspectives. The study comprised of a self-administered questionnaire that included descriptive questions. Data was collected based on the survey conducted via 100 students studying histology. Data was analyzed further qualitatively and quantitatively to elaborate on the difficulties in this area. Many of them strongly agreed that the lack of essential comprehension regarding using light and electron microscopes resulted in challenges with comprehending and identifying tissue samples for image identification due to inadequate anatomical knowledge. Moreover, according to students, some difficulties understood the topic, perception of new terminologies, and insufficient teaching strategies to grasp students' interests. They also agreed that improvement was needed in terms of the modes of teaching employed by histology teachers; they felt that modern education techniques based on practical tasks should be incorporated to stimulate student interest and make understanding histological concepts easier. The Institution should modify the teaching system to allocate more time to relevant subjects to make this subject matter more interesting. This survey-based study evaluated that students faced some challenges while studying the current curriculum of histology. From the student's perspective, it is identified that some changes are needed to improve the course curriculum and way of teaching to make it more understandable.